2013
DOI: 10.1038/ncomms3510
|View full text |Cite
|
Sign up to set email alerts
|

Functional evaluation of autism-associated mutations in NHE9

Abstract: Summary NHE9 (SLC9A9) is an endosomal cation/proton antiporter with orthologs in yeast and bacteria. Rare, missense substitutions in NHE9 are genetically linked with autism, but have not been functionally evaluated. Here we use evolutionary conservation analysis to build a model-structure of NHE9 based on the crystal structure of bacterial NhaA and use it to screen autism-associated variants in the human population first by phenotype complementation in yeast, followed by functional analysis in primary cortical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
170
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(182 citation statements)
references
References 62 publications
11
170
1
Order By: Relevance
“…Due to their distinct localization to specific types of organelles it is likely that intracellular NHEs play a critical part in the regulation of organellar pH. In support of this, overexpression or loss of intracellular NHEs alters organellar pH [113,35,130,80]. This concept is however challenged by studies where knock-down or loss of individual organelle-specific NHEs had no effect on pH [38,147,52].…”
Section: Intracellular Nhesmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to their distinct localization to specific types of organelles it is likely that intracellular NHEs play a critical part in the regulation of organellar pH. In support of this, overexpression or loss of intracellular NHEs alters organellar pH [113,35,130,80]. This concept is however challenged by studies where knock-down or loss of individual organelle-specific NHEs had no effect on pH [38,147,52].…”
Section: Intracellular Nhesmentioning
confidence: 99%
“…NHE9 localizes to sorting and recycling endosomes and its overexpression was shown to lead to endosomal alkalinization in COS-7 cells and primary astrocytes, whereas its knock-down induced endosomal acidification in primary astrocytes [113,80]. One exeption to the intracellular localization of NHE9 has thus far been reported.…”
Section: Slc9a9 -Nhe9mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, loss of NHE9 exchanger function as a result of mutations in SLC9A9 leads to hyperacidification of sorting endosomes (27). Functional evaluation of these autismassociated mutations in astrocytes showed that these cells lose their ability to clear glutamate to a significant extent as a consequence of dysregulated trafficking of glutamate transporter (GLAST) (27). Moreover, global knock-out SLC9A9 mice (Slc9a9 KO) show traits of autism spectrum and attention deficit hyperactivity disorder (29).…”
mentioning
confidence: 99%
“…The specific pH of each organelle is determined by a balance of V-ATPase-mediated proton pumping and a "proton leak" pathway (13)(14)(15). Several studies in yeast (16) and mammalian cells (14,15,(17)(18)(19) demonstrated that overexpression or knockdown of organellar NHEs leads to alkalinization or acidification of the organellar lumen, respectively, suggesting that these transporters provide a proton leak. The importance of organellar NHEs is underscored by mutations in NHE6 and NHE9 that lead to neurological disorders such as autism and epilepsy in humans (20,21).…”
mentioning
confidence: 99%